Peran SGLT2i terhadap Risiko Kardiorenal Pasien dengan atau Tanpa Diabetes Melitus Tipe 2 - Allen (PT Kalbe Farma Tbk., 2024)
Sodium-glucose Co-transporter 2 inhibitor (SGLT2i) is one of the antidiabetic classes recommended for patients with heart and kidney problems. Evidence-based studies show the benefits of SGLT2i extend to heart, kidney, or other metabolic diseases in patients without diabetes mellitus.